Capital Humano Configurado na Criança: projeto de formação do Banco Mundial para a infância da periferia do capitalismo - Guerra, Dhyovana (2024)
This thesis is part of the research line Education, Social Policies and the State, of the Graduate Program in Education at the State University of Western Paraná (Unioeste), Cascavel. It is a bibliographic and documentary research, with a qualitative approach, and the analysis of the sources is based on the perspective of historical-dialectical materialism. The documents make up our primary sources and were collected from the World Bank website and the Human Capital Project (HCP) page. The bibliographic research constitutes our secondary sources and was conducted on the Capes Periodicals Portal and Scielo, resulting in books, dissertations, theses and articles. The research problem of this thesis is the following question: how is the current human capital formation project proposed by the World Bank expressed and materialized? To answer this question, we outlined four specific objectives: a) Identify the socioeconomic and theoreticalideological foundations used by the World Bank to justify the need for human capital formation; b) Understand how the need for human capital formation is constructed in the socioeconomic and theoretical-ideological field; c) Comprehend how the justification for the existence of poverty is constructed in the socioeconomic and theoretical-ideological fields; d) Analyze how the human capital formation project proposed by the World Bank is expressed and materialized. As a result, we argue that the human capital formation project proposed by the World Bank is expressed in the concern for the education of poor children in the peripheral countries of capitalism and has materialized through the actions of the Human Capital Project (HCP), supported by an educational consensus around four dimensions: poverty, education, health and work. The socioeconomic and theoretical-ideological foundations of this educational consensus lie at the core of conservative thought, developed throughout the historical course of capital, which makes use of a well-elaborated conceptual framework, present in the theory of human capital and in the ideology of social Darwinism, for example. The socioeconomic and theoretical-ideological category that emerges from our study, and that expresses the core of this training project, is the Human Capital Configured in the Child, which, in essence, means producing and reproducing human formation from childhood, shaping a new profile of human capital in the peripheral countries of capitalism, with the objective of exploiting this labor force at a more opportune moment in adulthood.